Osseointegration: Switching On and Off Macrophages by a "Bridge‐Burning" Coating Improves Bone‐Implant Integration under Osteoporosis (Adv. Funct. Mater. 7/2021). (10th February 2021) - Wang, Zhenzhen; Niu, Yiming; Tian, Xuejiao; Yu, Na; Yin, Xiaoyu; Xing, Zhen; Li, Yurong; Dong, Lei; Wang, Chunming
Abstract : In article number 2007408, Lei Dong, Chunming Wang, and co‐workers invent a "bridge‐burning" bioactive coating to sequentially turn on and off inflammation on bone implants. This coating first instructs host macrophages to activate bone cells to promote healing and then receives signals from bone cells to kill macrophages for higher safety. It improves bone‐implant integration in mice with osteoporosis.